Peran Orang Tua Sebagai Teladan dalam Pendidikan Akhlak pada Anak - Harahap, Emilia Fitri; Khairunnisa, Khairunnisa; Araminta, Nabila; Sitorus, Masganti (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Education of morals for children is an important aspect in shaping their character and morals in the future. One of the factors that plays a major role in childrens moral education is parental role models. Parents as the main role models for the children have the responsibility to provide examples of good behavior, such a honesty, decipline, responsibility, and respect for other. This study aims to analyze the role of parental role models in shaping children’s morals through various approaches. The method use in this study is a qualitative descriptive with primary data and secondary data. The results of the study show that children tend to imitate their parent’s behavior, both in positive and negative aspects. Therefore, good parental role models are very important in shaping noble morals in children. These finding are expected to provide insight for parents regarding th importance of their behavior as example in children’s moral education.